2018
DOI: 10.1002/tcr.201800161
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ceria in the Design of Composite Materials for Elemental Mercury Removal

Abstract: The necessity to drastically act against mercury pollution has been emphatically addressed by the United Nations. Coal‐fired power plants contribute a great deal to the anthropogenic emissions; therefore, numerous sorbents/catalysts have been developed to remove elemental mercury (Hg0) from flue gases. Among them, ceria (CeO2) has attracted significant interest, due to its reversible Ce3+/Ce4+ redox pair, surface‐bound defects and acid‐base properties. The removal efficiency of Hg0 vapor depends among others, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 125 publications
(169 reference statements)
0
15
0
Order By: Relevance
“…The abundance of surface oxygen species has been repeatedly reported to improve Hg 0 removal efficiency, by providing the active sites for Hg 0 adsorption on the surface of sorbent/catalyst. 36 Finally, the O 1s and Mn 2p XPS spectra (Figure S6a,b) of the regenerated MnCe35 (see next sections) revealed that after the hightemperature regeneration process under N 2 atmosphere, the O b /O a and Mn 3+ /Mn 4+ ratios were reduced to 62.6 and 55.1%, respectively, possibly indicating, a favorable for Hg 0 removal, the correlation between the oxygen vacancies and the surfaceadsorbed oxygen species.…”
Section: ■ Experimental Sectionmentioning
confidence: 89%
See 1 more Smart Citation
“…The abundance of surface oxygen species has been repeatedly reported to improve Hg 0 removal efficiency, by providing the active sites for Hg 0 adsorption on the surface of sorbent/catalyst. 36 Finally, the O 1s and Mn 2p XPS spectra (Figure S6a,b) of the regenerated MnCe35 (see next sections) revealed that after the hightemperature regeneration process under N 2 atmosphere, the O b /O a and Mn 3+ /Mn 4+ ratios were reduced to 62.6 and 55.1%, respectively, possibly indicating, a favorable for Hg 0 removal, the correlation between the oxygen vacancies and the surfaceadsorbed oxygen species.…”
Section: ■ Experimental Sectionmentioning
confidence: 89%
“…Consequently, the modification of a certain morphology of α-MnO 2 by means of ceria nanoparticle decoration can significantly improve its Hg 0 removal activity at room temperature. This is exciting given that there are many studies reporting Mn−Ce composite materials for Hg 0 removal, 36 however operating at high temperatures (>150 °C).…”
Section: As Followsmentioning
confidence: 99%
“…Nanosized ceria finds a large variety of applications [71], and extensive reviews exist on the topic, especially relevant to catalysis [1] for energy [72,73] and environmental preservation [74] and remediation [75,76]. Therefore, here we will focus on the latest advancements described in the most recent years, with an emphasis on biological applications, for which the use of biomolecular templates for ceria nanostructures' assembly is particularly relevant.…”
Section: (Bio)applicationsmentioning
confidence: 99%
“…A variety of transition metal oxide catalysts for mercury oxidation, such as Mn, Cu, Fe, V, Ce and Co, have been employed in experiments. Ce‐based catalyst is regarded as one of the best candidates for Hg 0 oxidation removal with O 2 as the oxidant due to its active and facile Ce 3+ /Ce 4+ redox cycle and the corresponding outstanding oxygen storage capacity .…”
Section: Introductionmentioning
confidence: 99%